Physical and Sensory Long-Term Disabilities from Bothrops Snakebite Envenomings in Manaus, Western Brazilian Amazon - Fernández, Eduardo M. G.; Oliveira, Débora N.; Silva-Neto, Alexandre V.; Dávila, Rafaela N.; Lengler, Ligia; Sartim, Marco A.; Farias, Altair S.; Ferreira, Luiz C. L.; Carvalho, Érica da Silva; Wen, Fan H.; Murta, Felipe; Almeida-Val, Fernando; et al. (MDPI, 2025)
Snakebites caused by Bothrops snakes are the most prevalent in the Amazon region, causing local and systemic complications. Local complications are mostly represented by necrosis, secondary bacterial infection and compartment syndrome. There are reports of long-term disabilities, but their burden is poorly investigated. This study aims to describe and estimate the frequency of physical and sensory long-term disabilities from Bothrops snakebites in the Manaus Region, in the western Brazilian Amazon region. Participants were >18-years individuals that accepted to return to the hospital 3–12 months (average follow-up time of 195 days) after the discharge for neuromusculoskeletal, chronic pain and sensory assessments. Assessment of disability was also performed using the World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0). Factors associated with summary disability using WHODAS 2.0 were identified. Fifty participants were enrolled. A frequency of 20% of the participants reported difficulty in moving the affected limb (20%), and 23.7% reported difficulty in walking. Limitations of daily activities were reported by 26% of the patients. Decreased strength of the affected limb was observed in 22% of the patients. Decreased range of joint motion was seen in 20% of the patients. Chronic pain was reported in 48% of the patients. Tactile sensibility was decreased in 30%, thermal sensibility in 14%, painful sensibility (hypoalgesia) in 12%, kinetic-postural sensibility (hypokinesthesia) in 4% and vibratory sensibility was decreased or abolished in 16% of the participants. Cognition and mobility domains were those with the highest frequencies of participants with any degree of disability, each with 57%. The summary WHODAS 2.0 disability rate was 59%. Age > 59 years (p = 0.02)] was associated with protection against disability. Difficulty in moving the limb (p = 0.05), pain at the affected limb (p < 0.01), limitations of daily activities (p < 0.01) and decreased thermal sensibility (p = 0.05) were significantly associated with disability. The present study consists of the first follow-up investigation involving Bothrops snakebite patients related to long-term disabilities. These findings represent important data on Bothrops snakebites causing clinically significant long-term neuromusculoskeletal and sensory disabilities, resulting in reduced quality of life of the patients.
Keywords: Bothrops; physical disability; public health; sensory disability; snakebites